2010
DOI: 10.1111/j.1365-2753.2009.01221.x
|View full text |Cite
|
Sign up to set email alerts
|

An assessment of drug administration compliance in a university hospital centre

Abstract: Compliance rates at various separately evaluated stages in 2008 were relatively satisfactory. There is, however, room for improvement in total compliance. The introduction of simple tools and adapted communication strategies led to a sizeable improvement in the medication process at our facility.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 14 publications
0
15
0
Order By: Relevance
“…Although 20 studies reported provider education as part of their intervention to reduce pediatric medication errors, 14 studies 31,34,37,40,56,60,65,71,75,76,78,82,85,87 used education as their main intervention to reduce pediatric medication errors. Seven of these 14 studies collected data for #3 months after implementing the intervention and 2 did not report on the months of systems for all providers.…”
Section: Data Synthesis For Specific Interventionsmentioning
confidence: 99%
“…Although 20 studies reported provider education as part of their intervention to reduce pediatric medication errors, 14 studies 31,34,37,40,56,60,65,71,75,76,78,82,85,87 used education as their main intervention to reduce pediatric medication errors. Seven of these 14 studies collected data for #3 months after implementing the intervention and 2 did not report on the months of systems for all providers.…”
Section: Data Synthesis For Specific Interventionsmentioning
confidence: 99%
“…The six intervention types included: technology (n = 38), organizational (n = 16), [56][57][58][59][60][61][62][63][64][65][66][67][68][69][70][71] personnel (n = 13), [72][73][74][75][76][77][78][79][80][81][82][83][84] pharmacy (n = 9), [85][86][87][88][89][90][91][92][93] hazard and risk analysis (n = 8), 10,[93][94][95][96][97][98][99] and multifactorial (i.e. a combination of any of the previous themes; n = 18).…”
Section: Overview Of Included Studiesmentioning
confidence: 99%
“…Development of preformatted medication order sheets [56][57][58][59][60][61][62][63][64] Medication distribution and supply (n = 6) Preparation of prediluted medications for administration [65][66][67][68][69][70] Nurse prescribing (n = 1) Transcription of paper-based orders to electronic orders by nursing staff 71 Personnel (n = 13) Staff education (n = 13) Personalized feedback of medication prescribing errors [72][73][74][75][76][77][78][79][80][81][82][83][84] Pharmacy (n = 9) Ward based (n = 6) Interventions identified through introduction of ward-based paediatric/neonatal clinical pharmacy service [85][86][87][88][89][90] Dispensary based (n = 3) Interventions identified through dispensary-based pharmacy service [91][92][93] Hazard and risk analysis (n = 8) Quality improvement tools (n = 4) Use of failure modes, effects, and criticality analyses to redesign care processes 10,[95][96][97] Error detection tools (n = 3) Automated detection of medication errors 93,…”
Section: Intervention Type Example Of Intervention Referencesmentioning
confidence: 99%
“…Yet, compliance with the protocol proceedings for safe injectable medication administration is low (Alemanni et al, 2010;Barthelemy et al, 2013;Choo et al, 2013;Schilp et al, 2014;Schutijser et al, 2018;Westbrook et al, 2011). Especially the compliance with the double check proceeding is between 45 and 90% and needs improvement (Alsulami et al, 2014;Kellett and Gottwald, 2015;Schilp et al, 2014;Schutijser et al, 2018).…”
Section: Introductionmentioning
confidence: 99%